Influence Islamic leadership, Commitment Organization, Prevention Fraud Report Finance and Systems Information Accountancy to Quality Report Finance - Egi Gumala Sari (Yayasan Az Zukhruf Cendikia, 2024)
Purpose – This study aims to analyze the influence of Islamic leadership, organizational commitment, financial fraud prevention, and accounting information systems on the quality of financial reports. Design/methodology/approach – The study uses primary data with a sample of 32 respondents, selected through random sampling. The research employs quantitative methods to assess the relationships between the variables, analyzing the data to determine the impact on financial report quality. Findings – The results indicate that Islamic leadership has a positive and significant effect on the quality of financial reports. Organizational commitment has a positive but not significant effect, financial fraud prevention has a negative and not significant effect, while accounting information systems have a positive and significant effect on the quality of financial reports. Research limitations/implications – The study is limited by its relatively small sample size of 32 respondents, which may impact the generalizability of the findings. Future research could expand the sample or explore additional variables to better understand the factors affecting financial report quality in various contexts.